Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

If f(x) = 2x – 1 and g(x) = log x, compute (f – g) (x)

Sagot :

Answer:

(f-g) (x) = 2x – 1 - log(x)

Step-by-step explanation:

f(x) = 2x – 1

g(x) = log x

We are given the two function and want to subtract g(x) from f(x)

(f-g) (x) = 2x – 1 - log(x)